(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
BackgroundMutilation killings, especially those in which the victim has been disembowelled, are among the most vio lent forms of homicide and are generally believed to be the work of serial killers. These are not typical forensic pathology cases, illustrating deficiencies in legal, ethical, and investigative structures. To achieve better investigative and judicial outcomes, it is essential to understand the forensic, psychiatric, and legal complexities of these cases. MethodsNational and International landmark case laws, medico-legal autopsy reports and court proceedings concern ing mutilation homicides in which evisceration is the principal modality of assault were narratively reviewed in this article. Electronic databases, such as PubMed, Scopus, and legal repositories, were searched using a defined set of search terms related to mutilation, autopsy findings, offender profiling, ethics, and evaluation. ResultsThe findings of a forensic autopsy contribute decisively to the establishment of the cause and manner of death and also to differentiating ante mortem from post-mortem mutilation. Ritualistic behaviour and related psychopathol ogy were often linked to specific organ-targeting patterns. Ethical issues arose about mutilated corpses, collateral trauma to forensic pathologists and the open-court presentation of gruesome evidence. The court’s scrutiny highlighted the ongoing challenges in critically evaluating complex scientific evidence without compromising the accused’s right to a fair trial. ConclusionThe findings emphasise the imperative of sound cross-disciplinary cooperation in an in-depth homicide investigation involving forensic medicine, law, and ethics at both investigative and court stages. Scientific rigour informed by ethical sensitivity and judicial wisdom will help us deal more appropriately, justly, and accountably with these cases.